Factors of Severity Dengue Hemorrhagic Fever during the Covid-19 Pandemic; A Case Control Study in Buleleng, Bali - I Gede Peri Arista; Anak Agung Sagung Sawitri; I Made Suganda Yatra (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: The incidence of severe Dengue Hemorrhagic Fever (DHF) in Buleleng District during the COVID-19 pandemic was very high. Our study aimed to analyze the relationship between age, sex, area of residence, type of hospital, season of occurrence and time period with the incidence of severe DHF.Methods: We conducted a case-control study. Our study sample was 135 with a ratio of cases to controls of 1:2. We collected secondary data obtained from the DHF register data of the Buleleng District Health Office in 2019 to 2020. We performed data processing and analysis using the SPSS version 22. Descriptive analysis using a cross-table distribution and inferential analysis using Chi-Square or Fisher-Exact tests with p values <0.05 or Confident Interval (CI) is 95%.Result: We found more severe cases of DHF in the group aged 1-12 years, male, living in rural areas, undergoing hospitalization in private hospitals, during the rainy season and during the COVID-19 pandemic period. Age group 1-12 years (OR: 4.3 95%CI: 1.9-9.4, p value=0,000) and rainy season (OR: 2.4 95%CI: 1.1-5.2, p value=0,025) were significantly associated with the severity of DHF.Conclusion: The age group of 1-12 years and the rainy season are risk factors for the severity of DHF during the COVID-19 pandemic. It is necessary to disseminate early awareness of DHF at the elementary school level and empower parents in maintaining the health condition of their children.